INVESTIGATING TEACHERS' INTERPERSONAL BEHAVIORS IN PROMOTING EFL STUDENTS' PARTICIPATION - Dara Fitria Munzaki, - (2019)
Interpersonal behavior is part of teachers' professional development. Interpersonal behavior describes the interaction in the classrooms which indicates personality. Positive personality is one of the influential factors in promoting students' participation and classroom engagement. This present study focuses on investigating teachers' interpersonal behaviors in EFL classrooms that promote students' participation during classroom activities. MITB (Model for Interpersonal Teacher Behavior) framework was used in this study in which the proximity and influence dimensions were explored. This study was conducted in EFL classrooms by inviting Indonesian junior high school students. Trying to cover students' points of view, the present study utilized three research instruments: observation, questionnaire, and semi-structured interview. The results of which were reported descriptively. The results show that the teachers' interpersonal behaviors were indicated to have positive contributions to provide participative classrooms. This study highlighted that the teachers' positive behaviors (leadership, helping/friendly, and understanding: proximity and influence dimensions) promoted students' participation in EFL classrooms. Further, the teachers' positive personalities are useful to facilitate and promote students' participation in the classrooms. Meanwhile, admonishing and strict sectors were found and they were useful to control classroom management and discipline students. In addition, interpersonal behaviors were found to be an important aspect of teachers' professional development to enhance a student-teacher relationship, provide a better teaching quality, and facilitate students' engagement in EFL classrooms. Further, this study recommended that further researches exploring interpersonal behaviors in different levels of education, such as a university, in the Indonesian context. Keywords: Interpersonal behaviors, students' participation, EFL classrooms, positive behaviors